2020
DOI: 10.1016/j.cct.2020.106103
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design, and methods of the Autism Centers of Excellence (ACE) network Study of Oxytocin in Autism to improve Reciprocal Social Behaviors (SOARS-B)

Abstract: To describe the rationale, design, and methods of the Autism Centers of Excellence (ACE) network Study of Oxytocin in Autism to improve Reciprocal Social Behaviors (SOARS-B). Method: This phase 2 clinical trial was designed to evaluate the use of intranasal oxytocin treatment to improve social difficulties in individuals with autism spectrum disorder (ASD). In total, 290 participants ages 3 to 17 years with a DSM-5 diagnosis of ASD were enrolled to receive 24 weeks of treatment with either oxytocin or a matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…A full description of the SOARS-B clinical trial and study population has been previously reported 18, 50 . Briefly, 355 children and adolescents were screened for study inclusion, with 290 individuals with ASD enrolled and randomized 1:1 to intranasal placebo or oxytocin spray in a multi-site clinical trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A full description of the SOARS-B clinical trial and study population has been previously reported 18, 50 . Briefly, 355 children and adolescents were screened for study inclusion, with 290 individuals with ASD enrolled and randomized 1:1 to intranasal placebo or oxytocin spray in a multi-site clinical trial.…”
Section: Methodsmentioning
confidence: 99%
“…All batches were background-corrected and quantile-normalized together using limma’s neqc function. Samples were excluded from analyses if they were flagged as a sample swap in analysis of each omics dataset or if they came from an individual that had an underlying genetic condition, as defined in the SOARS-B study 18, 50 . Probes were excluded if they displayed poor mapping quality or were not detected across all samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, as illustrated by a recent meta-analysis, there does seem to be overall beneficial effects of OXT on social symptoms of ASD, although this review included both children and adults [90]. There is also some promising research looking at the role of OXT in combination with other treatment modalities including behavior therapy and probiotics, with clinical trials in this area ongoing [91,92]. It is also likely that the effects of OXT in ASD are modulated by age, gender, and possibly genetic factors [77,79,90].…”
Section: Oxytocinmentioning
confidence: 99%
“…We also note that a large-scale multi-site trial of the behavioral effects of oxytocin versus placebo is underway by the Study of Oxytocin in Autism to Improve Reciprocal Social Behaviors (SOARS-B; clinical trial identifier NCT01944046). One paper describing the rationale and methods for the trial has been published [93].…”
Section: Current Research Combining Oxytocin and Behavioral Interventions In Asdmentioning
confidence: 99%